Notes of memories: Fostering social interaction, activity and reminiscence through an interactive music exergame developed for people with dementia and their caregivers. Issue 5 (1st October 2021) - Unbehaun, David; Taugerbeck, Sebastian; Aal, Konstantin; Vaziri, Daryoush Daniel; Lehmann, Jasmin; Tolmie, Peter; Wieching, Rainer; Wulf, Volker
ABSTRACT: This paper presents the outcomes of an exploratory study focused on the evaluation of an interactive music exergame for People with Dementia (PwD) and their caregivers. PwD tend to isolate themselves from the outside world, therefore carers need to develop strategies to maintain communication with them. Studies indicate that music–based activities provide an effective way to achieve social interaction with PwD. At the same time, physical activity plays a major role in dementia-related interventions because it can slow down progression and provide meaningful stimulation. Our developed interactive music game bounds these two concerns together; we evaluated the system afterwards regarding its individual and social impact and its integration into the daily routines of both PwD and their caregivers, focusing on its capacity to provide both enjoyment and relief from some of the effects of dementia. Qualitative data collected over 4 months confirmed the valuable impact of music-based interventions of PwD. Of particular note was how PwD used the game to improve or maintain their physical condition while recovering past memories and an interest in social interaction.